ALAM KESADARAN PADA TOKOH UTAMA DALAM NOVEL EGOSENTRIS KARYA SYAHID MUHAMMAD: TINJAUAN PSIKOANALISIS GUSTAV JUNG - Nurhalisa Nurhalisa; Nensilianti Nensilianti; Hajrah Hajrah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2023)
The Nature of Consciousness in the Main Character in the Egocentric Novel by Syahid Muhammad Psychoanalytic Review by Carl Gustav Jung. The purpose of this research is to identify the nature of consciousness based on the personality of the main character in the novel Egicentric by Syahid Muhammad using Carl Gustav Jung's psychoanalytic theory. This research is a descriptive qualitative research with using psychoanalytic theory. The results of this study indicate the nature of consciousness, namely mental attitude, found introverted personality from Fatih's indifferent and insecure personality, while exnoverted personality was found from Fatih's personality who pays attention to environmental conditions. feeling introversion from the aura of melancholy he emits, the type of sensing introversion seen from Fatih's closed personality.